Construction and evaluation of ovalbumin-pullulan nanogels as a potential delivery carrier for curcumin. (15th January 2022) - Zeng, Qi; Zeng, Wenhao; Jin, Yongguo; Sheng, Long
Highlights: Ovalbumin-pullulan nanogels for loading curcumin were firstly fabricated. The proposed nanogels facilitated the controlled release of curcumin. Ovalbumin-pullulan nanogels loading curcumin exhibited excellent storage stability. Abstract: Preparation of protein/polysaccharide nanocomplexes for delivering environment-sensitive bioactive compounds is significant in the fields of functional foods and pharmaceuticals. In this work, ovalbumin-pullulan (OVA-Pul) nanogels were fabricated through Maillard reaction combined with heat treatment. The results of SDS-PAGE, circular dichroism and conjugation yield (84.96%) confirmed the covalent crosslinking of ovalbumin to pullulan. Dynamic light scattering measurements indicated that nanogels and curcumin-loaded nanogels exhibited small particle diameter at around 190 nm and 160 nm, and excellent polydispersity index at 0.227 and 0.146, respectively. OVA-Pul nanogels showed good encapsulation efficiency (88.38%) and loading capacity (8.78%) for curcumin. Transmission electron microscope observations and in vitro gastrointestinal digestion suggested that OVA-Pul nanogels facilitated the controlled release of curcumin and the spherical structure of curcumin-loaded nanogels was damaged during digestion. Notably, both nanogels and curcumin-loaded nanogels showed desirable storage stability during 30 d. Hence, OVA-Pul nanogels have the potential for effectively delivering nutrients and drugs.